Sulfite Reductase Co-suppression in Tobacco Reveals Detoxification Mechanisms and Downstream Responses Comparable to Sulfate Starvation - Naumann, Marcel; Hubberten, Hans-Michael; Watanabe, Mutsumi; Hänsch, Robert; Schöttler, Mark Aurel; Hoefgen, Rainer (Frontiers in Plant Science, 2018)
Sulfite reductase (SIR) is a key enzyme in higher plants in the assimilatory sulfate reduction pathway. SIR, being exclusively localized in plastids, catalyzes the reduction of sulfite (SO32-) to sulfide (S2-) and is essential for plant life. We characterized transgenic plants leading to co-suppression of the SIR gene in tobacco (Nicotiana tabacum cv. Samsun NN). Co-suppression resulted in reduced but not completely extinguished expression of SIR and in a reduction of SIR activity to about 20% to 50% of the activity in control plants. The reduction of SIR activity caused chlorotic and necrotic phenotypes in tobacco leaves, but with varying phenotype strength even among clones and increasing from young to old leaves. In transgenic plants compared to control plants, metabolite levels upstream of SIR accumulated, such as sulfite, sulfate and thiosulfate. The levels of downstream metabolites were reduced, such as cysteine, glutathione (GSH) and methionine. This metabolic signature resembles a sulfate deprivation phenotype as corroborated by the fact that O-acetylserine (OAS) accumulated. Further, chlorophyll contents, photosynthetic electron transport, and the contents of carbohydrates such as starch, sucrose, fructose, and glucose were reduced. Amino acid compositions were altered in a complex manner due to the reduction of contents of cysteine, and to some extent methionine. Interestingly, sulfide levels remained constant indicating that sulfide homeostasis is crucial for plant performance and survival. Additionally, this allows concluding that sulfide does not act as a signal in this context to control sulfate uptake and assimilation. The accumulation of upstream compounds hints at detoxification mechanisms and, additionally, a control exerted by the downstream metabolites on the sulfate uptake and assimilation system. Co-suppression lines showed increased sensitivity to additionally imposed stresses probably due to the accumulation of reactive compounds because of insufficient detoxification in combination with reduced GSH levels.